Etika Bisnis dalam Hukum Islam: Implikasi terhadap Praktik Bisnis Modern - Mufarrochah, Sylvia; Putri, Febri Falisa; Murtadho, Achmad; Assari, Elsa (Universitas Semarang, 2025)
This research aims to analyze modern business practices within Islamic business ethics and the challenges and opportunities in implementing modern business practices from the perspective of business ethics in Islamic law. The implications of the application of Islamic business ethics in modern business practices can be seen in efforts to create a balance between profit and morality, as well as addressing socio-economic problems that often arise in today's business world, such as unfair distribution of wealth, exploitation of labor, and environmental damage. The urgency of this problem is increasingly relevant when today's business world prioritizes the principle of profitability which sometimes conflicts with ethical values. Phenomena such as market manipulation, monopolistic practices, and exploitation carried out by large companies show the importance of implementing business ethics in Islam that emphasizes balance and sustainability. Therefore, it is important to conduct a more in-depth study of how the principles of Islamic business ethics can be adapted and integrated into modern business practices so that they not only provide economic benefits but also provide broad social benefits to society. The implementation of these ethics can also help increase public trust in the business world and create a more equitable and sustainable business environment. This type of research will use a qualitative approach and literature analysis to analyze Islamic economic values and business ethics. The qualitative approach involves a thorough examination of primary and secondary sources related to Islamic economic principles and ethics. This process will include an analysis of texts related to the topic. Penelitian ini bertujuan untuk analisis terhadap praktik bisnis modern dalam etika bisnis Islam dan tantangan dan peluang dalam menerapkan praktik bisnis modern dalam perspektif etika bisnis dalam hukum Islam. Implikasi dari penerapan etika bisnis Islam dalam praktik bisnis modern dapat dilihat dalam upaya menciptakan keseimbangan antara profit dan moralitas, serta menanggulangi masalah sosial-ekonomi yang sering muncul dalam dunia bisnis saat ini, seperti ketidakadilan distribusi kekayaan, eksploitasi tenaga kerja, dan kerusakan lingkungan. Urgensi permasalahan ini semakin relevan ketika dunia bisnis masa kini mengedepankan prinsip profitabilitas yang kadang bertentangan dengan nilai-nilai etika. Fenomena seperti manipulasi pasar, praktik monopoli, serta eksploitasi yang dilakukan oleh perusahaan besar menunjukkan pentingnya penerapan etika bisnis dalam Islam yang menekankan pada keseimbangan dan keberlanjutan. Penting untuk melakukan kajian lebih mendalam tentang bagaimana prinsip-prinsip etika bisnis Islam dapat diadaptasi dan diintegrasikan dalam praktik bisnis modern, agar tidak hanya memberikan keuntungan ekonomi, tetapi juga memberikan manfaat sosial yang luas bagi masyarakat. Implementasi etika ini juga dapat membantu meningkatkan kepercayaan publik terhadap dunia bisnis dan menciptakan lingkungan usaha yang lebih adil dan berkelanjutan. Jenis penelitian ini akan menggunakan pendekatan kualitatif dan analisis pustaka untuk menganalisis nilai-nilai ekonomi dan etika bisnis Islam. Pendekatan kualitatif melibatkan pemeriksaan menyeluruh terhadap sumber-sumber primer dan sekunder yang terkait dengan prinsip-prinsip ekonomi dan etika Islam. Proses ini akan mencakup analisis teks-teks yang terkait dengan topik tersebut.